Die Erinnerungsgeschichte der Verfolgung ungarischer Galeerensklaven protestantischen Bekenntnisses im Deutschland des 18. Jahrhunderts - Verók, Attila (Acta Neerlandica, 2026)
In the long 18th century described as the period of “peaceful Re-Catholicization” or “Catholic Restoration” in the writings about the ecclesiastical history of different congregations, the Roman Catholic Church used every means to push Protestants into the background and to render their lives impossible. As a result of intensified ReCatholicization, diverse means were employed to confront the communities and individuals, from the occupation of churches or schools and collective punishments, through the public humiliation and terrorization of individuals, to bloody torture and the annihilation of their livelihood. The partly violent spreading of Catholicism resulted in many controversial cases in the Carpathian Basin, which were reported on many publications in Western Europe. The examination of the early printed books in the Lutheran collection of books in Halle (Franckesche Stiftung) has brought numerous relevant texts from a Hungarian perspective to the surface, which allow studying the danger-fraught life circumstances of Protestants in the Carpathian Basin in the 18th century through the eyes of an external observer.